Challenging Giant Insular Gliomas With Brain Mapping: Evaluation of Neurosurgical, Neurological, Neuropsychological, and Quality of Life Results in a Large Mono-Institutional Series - Rossi, Marco; Gay, Lorenzo; Conti Nibali, Marco; Sciortino, Tommaso; Ambrogi, Federico; Leonetti, Antonella; Puglisi, Guglielmo; Howells, Henrietta; Zito, Paola; Villa, Federico; Ciroi, Gjulio; Riva, Marco; et al. (Frontiers in Oncology, 2021)
Objective Giant insular tumors are commonly not amenable to complete resection and are associated with a high postoperative morbidity rate. Transcortical approach and brain mapping techniques allow to identify peri-insular functional networks and, with neurophysiological monitoring, to reduce vascular-associated insults. Cognitive functions to be mapped are still under debate, and the analysis of the functional risk of surgery is currently limited to neurological examination. This work aimed to investigate the neurosurgical outcome (extent of resection, EOR) and functional impact of giant insular gliomas resection, focusing on neuropsychological and Quality of Life (QoL) outcomes. Methods In our retrospective analysis, we included all patients admitted in a five-year period with a radiological diagnosis of giant insular glioma. A transcortical approach was adopted in all cases. Resections were pursued up to functional boundaries defined intraoperatively by brain mapping techniques. We examined clinical, radiological, and intra-operative factors possibly affecting EOR and postoperative neurological, neuropsychological, and Quality of Life (QoL) outcomes. Results We finally enrolled 95 patients in the analysis. Mean EOR was 92.3%. A Gross Total Resection (GTR) was obtained in 70 cases (73.7%). Five patients reported permanent morbidity (aphasia in 3, 3.2%, and superior quadrantanopia in 2, 2.1%). Suboptimal EOR associated with poor seizures control postoperatively. Extensive intraoperative mapping (inclusive of cognitive, visual, and haptic functions) decreased long-term neurological, neuropsychological, and QoL morbidity and increased EOR. Tumor infiltration of deep perforators (vessels arising either medial to lenticulostriate arteries through the anterior perforated substance or from the anterior choroidal artery) associated with a higher chance of postoperative ischemia in consonant areas, with the persistence of new-onset motor deficits 1-month post-op, and with minor EOR. Ischemic insults in eloquent sites represented the leading factor for long-term neurological and neuropsychological morbidity. Conclusion In giant insular gliomas, the use of a transcortical approach with extensive brain mapping under awake anesthesia ensures broad insular exposure and extension of the surgical resection preserving patients’ functional integrity. The relation between tumor mass and deep perforators predicts perioperative ischemic insults, the most relevant risk factor for long-term and permanent postoperative morbidity.